A structural analysis of the bent kinetoplast DNA from Crithidia fasciculata by high resolution chemical probing. - McCarthy, J G (1993)
The chemical probes potassium permanganate (KMnO4) and diethylpyrocarbonate (DEPC) have been used to study the conformation of bent kinetoplast DNA from Crithidia fasciculata at different temperatures. Chemical reactivity data shows that the numerous short A-tracts of this bent DNA adopt a similar structure at 43 degrees C. This conformation appears to be very similar to the conformation of A-tracts in DNA exhibiting normal gel mobility. The A-tract structure detected by chemical probing is characterized by a high degree of base stacking on the thymine strand, and by an abrupt conformational change at the 3' end of the adenine strand. In general, no major alteration of this A-tract specific structure was detected between 4-53 degrees C. However, probing with KMnO4 revealed two unusual features of the C. fasciculata sequence that may contribute to the highly aberrant gel mobility of this DNA: 1) the B DNA/A-tract junction 5' dC/A3-6 3'. 5' dT3-6/G 3' is disproportionately represented and is conformationally distinct from other 5' end junctions, and 2) low temperature favors a novel strand-specific conformational distortion over a 20 base pair region of the bent kinetoplast DNA. Presence of the minor groove binding drug distamycin had little detectable effect on the A-tract conformation. However, distamycin did inhibit formation of the novel KMnO4 sensitive low temperature structure and partially eliminated the anomalous gel mobility of the kinetoplast DNA. Finally, we describe a simple and reproducible procedure for the production of an adenine-specific chemical DNA sequence ladder.